(untitled) (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted at the experimental field of Sher-e-Bangla Agricultural University, Dhaka during the period from October 2010 to March 2011 to study the feasibility of replacing chemical fertilizer by using organic fertilizer in wheat. The experiment comprised of 10 treatments, such as T0: Control condition; T1: All chemical fertilizer as recommended dose; T2: Cowdung as recommended dose; T3: Compost as recommended dose; T4: ½ Cowdung + ½ Compost; T5: Cowdung + Compost; T6: Cowdung + ½ Chemical fertilizer; T7: Compost + ½ Chemical fertilizer; T8: Cowdung + Compost +½ Chemical fertilizer and T9: ½ Cowdung + ½ Compost + ½ Chemical fertilizer. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. At 30, 50, 70, 90 and 110 (Days After Sowing) DAS, the highest dry matter content plant-1 was recorded from T1 (0.30 g, 3.87 g, 8.84 g, 19.58 g and 30.18 g), whereas the lowest weight from T0 (0.18 g, 2.49 g, 6.50 g, 11.80 g and 18.08 g). At 30-50 DAS, the highest (Crop Growth Rate) CGR was found from T1 (5.35 g m-2day-1), while the lowest CGR from T0 (3.46 g m-2day-1). At 50-70 DAS, the highest CGR was found from T7 (8.34 g m-2day-1), while the lowest CGR from T0 (6.70 g m-2day-1). At 70-90 DAS, the highest CGR was found from T1 (17.89 g m-2day-1), while the lowest CGR from T0 (8.83 g m-2day-1). At 90-110 DAS, the highest CGR was found from T8 (18.69 g m-2day-1), while the lowest CGR from T0 (10.47 g m-2day-1). At 30-50 DAS, the highest RGR was found from T3 (0.134 g g-1 day-1) and the lowest RGR from T5 and T8 (0.127 g g-1 day-1). At 50-70 DAS, the highest RGR was found from T3 (0.049 g g-1 day-1) and the lowest RGR from T9 (0.041 g g-1 day-1). At 70-90 DAS, the highest RGR was found from T3 (0.040 g g-1 day-1) and the lowest RGR from T0 (0.030 g g-1 day-1). At 90-110 DAS, the highest (Relative Growth Rate) RGR was found from T3 (0.026 g g-1 day-1) and the lowest RGR from T0 (0.021 g g-1 day-1). The longest spike (19.86 cm), highest grain yield (3.71 t ha-1) and highest straw yield (5.78 t ha-1) was attained from T1 and the shortest spike (14.33 cm), lowest grain yield (2.06 t ha-1) and lowest straw yield (4.49 t ha-1) from T0. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22032 J. Environ. Sci. & Natural Resources, 6(1): 07-10 2013